Energia termonuclear no São Francisco: perspectivas e restrições - CABRAL, Anya Dantas (2016)
By 2008 the National Energy Plan for 2010 anounced the need to expand the nuclear park with the finishing of Angra 3 and the settiing up of least four new nuclear plants, from which two in the Southeast region and two in the Northeast. Location studies pointed out the São Francisco river margins as ideals to hold tbe Northeast componente. Nuclear energy, more than providing firm energy, was an environmental alternative better than the conventional ones as in regard to CO2 emissions, as well as for the price of KWA. The construction of nuclear plants was central to a Project of valuing the strategic role of nuclear power for the international role of the country. The new centrals should make feasible new mining projects and for treating uranium. The economic crisis untaped in 2008 and the nuclear accident at Fukushima, besides de water shortage in the Northeast summed with economic crisis in Brazil changing the conditions por installing new nuclear plants in the country. From an historic – dialectics approach this study aims to verify the actual conditions for a nuclear plant in the mid-São Francisco basin with its environmental and economic implications, given the presente operational conditions of electric energy operations.